Heterogeneity in education and training sixth release of the KOF youth labour market index - Filippo Pusterla; Maria Esther Oswald-Egg (ETH Zurich, KOF Swiss Economic Institute, 2019)
This report describes the sixth release of the KOF Youth Labour Market Index (KOF YLMI). The KOF YLMI is an index consisting of 12 indicators that captures the situation of the youth on the labour market. We update the data on a yearly basis, so that in this release the available data ranges from 1991 to 2017. The updated values are also available in the interactive web tool1, which allows comparisons to be made between countries or country groups over time. Users can select their countries of interest and download the created graphs and scoreboards. In the sixth release we expand the data series to the year 2017, and the data sources continue to be the International Labour Organization (ILO), the Organisation for Economic Co-operation and Development (OECD) and Eurostat. The newest data from 2017 shows a clear improvement of the KOF YLMI around the globe. There were changes in all the four dimensions - namely Activity State, Working Conditions, Education and Transition Smoothness - where most of the changes entail an improvement. The new top performer is Switzerland, which has surpassed Denmark in the country rankings; the third best performer is Latvia, a country that has improved substantially. Overall, the improvements along the country rankings are particularly pronounced in Eastern European countries.
Keywords: 330